Hubungan EQ Siswa Usia 9-11 Tahun Terhadap Hasil Belajar Pendidikan Jasmani Siswa Sekolah Dasar - Farkhan Restu Hidayatulloh; Drastiana Siwi Maheswari (Jurnal MensSana, 2026)
Physical education has a strategic role in shaping students holistic development; however, emotional intelligence is often not the main focus in the learning process. This study aims to analyze the relationship between emotional intelligence and physical education learning outcomes among elementary school students. This research employed a quantitative approach with a correlational method, involving a population of 113 fourth and fifth grade students. Using purposive sampling, 112 students aged 9–11 years were selected as the sample. The research instruments included a Likert-scale emotional intelligence questionnaire and documentation of physical education learning outcomes. Data were analyzed using SPSS version 24, starting with the Kolmogorov-Smirnov normality test, which indicated that the data were not normally distributed. Therefore, hypothesis testing was conducted using Spearman Rank correlation analysis. The results showed a correlation coefficient of 0.026 with a significance value of 0.782 (p > 0.05). This indicates that there is no significant relationship between emotional intelligence and physical education learning outcomes among elementary school students. Thus, emotional intelligence is not a primary factor influencing physical education learning outcomes in this study.